Liquidity and Asset Prices: How Strong Are the Linkages? - Christian Dreger; Jürgen Wolters (Review of Economics and Finance, 2011)
The appropriate design of monetary policy in integrated financial markets is one of the most challenging areas for central banks. One hot topic is whether the increase in liquidity has contributed to the formation of price bubbles in asset markets in the years preceding the financial crisis. If linkages are strong, the inclusion of asset prices in the monetary policy rule may limit speculative runs and negative spillovers to the real economy in the future. To examine the impacts of liquidity shocks on real share and house prices, VAR models are specified for the US and the euro area, as well as global VARs to control for international feedback. The analysis points to some impact of liquidity shocks on house prices, but the effect is restricted to the US. Stock market prices are not affected. Thus, the results suggest that the link between liquidity and asset prices is fragile and far from being obvious.
Additional information: This publication was produced as part of the FINESS project, funded by the European Commission through the 7th Framework Programme under contract no. 217266 (http://www.finess-web.eu/).; info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: E44; G10; C32; C52; 330; Liquidity shocks; Asset prices; GVAR analysis; Monetary policy